Increased density of Thalassiosira sp with different doses of silicate fertilizer - Erlangga, Erlangga; Andira, Ayu; erniati, erniati; mahdaliana, mahdaliana; muliani, muliani (Acta Aquatica: Aquatic Sciences Journal, 2021)
The research was conducted in 11-25 July 2020 at Water Quality and Fish Nutrition Laboratory, Faculty of Agriculture, University of Malikussaleh. The research design used was Completely Randomized Design (CRD) non factorial with 4 treatments and 3 replications. With treatment A: culture of Thalassiosira sp with 15 ppm silicate fertilizer, treatment B: culture of Thalassiosira sp with 17 ppm silicate fertilizer, treatment C: culture of Thalassiosira sp with 19 ppm silicate fertilizer, treatment D: culture of Thalassiosira sp with 21 ppm silicate fertilizer. The result showed that the effect of silicate fertilizer with different dosage gave a different significant to cells Thalassiosira sp density and significantly different to cells Thalassiosira sp peak populasion. The highest average cell density value was found in treatment A (15 ppm) of 419,10 x 104 cells/ml, then treatment B (17 ppm) of 256,67 x 104 cells/ml, followed by treatment C (19 ppm) of 216,29 x 104 cells/ml and treatment D (21 ppm) of 102,90 x 104 cells/ml. The highest cell populasion peak is found in treatment A (15 ppm) of 689,67 x 104 cells/ml, then treatment B (17 ppm) of 389,33 x 104 cells/ml, followed by treatment C (19 ppm) of 388 x 104 cells/ml and treatment D (21 ppm) of 156 x 104 cells/ml. the water quality of the study in standard condision is pH 6,9-8, salinity 32 ppt, light intensity 800-2500 lux, and temperature 25-290C.Keywords: Density; Thalassiosira; silicate